Low-Calcium fly ash-based geopolymer concrete: Long-term properties - Wallah, Steenie; Rangan, B. Vijaya (2006)
From 2001, we have conducted some important research on the development, manufacture, behaviour, and applications of Low-Calcium Fly Ash-Based Geopolymer Concrete. This concrete uses no Portland cement; instead, we use the low-calcium fly ash from a local coal burning power station as a source material to make the binder necessary to manufacture concrete.Concrete usage around the globe is second only to water. An important ingredient in the conventional concrete is the Portland cement. The production of one ton of cement emits approximately one ton of carbon dioxide to the atmosphere. Moreover, cement production is not only highly energy-intensive, next to steel and aluminium, but also consumes significant amount of natural resources. In order to meet infrastructure developments, the usage of concrete is on the increase. Do we build additional cement plants to meet this increase in demand for concrete, or find alternative binders to make concrete? On the other hand, already huge volumes of fly ash are generated around the world; most of the fly ash is not effectively used, and a large part of it is disposed in landfills. As the need for power increases, the volume of fly ash would increase.Both the above issues are addressed in our work. We have covered significant area in our work, and developed the know-how to manufacture low-calcium fly ash-based geopolymer concrete. Our research has already been published in more than 30 technical papers in various international venues.This Research Report describes the long-term properties of low-calcium fly ash-based geopolymer concrete. Earlier, the Research Report GC1 presented the development,the mixture proportions, and the short-term properties of low-calcium fly ash-based geopolymerconcrete. A subsequent Research Report GC3 covers the behaviour and strength of reinforced geopolymer concrete structural beams and columns.Heat-cured low-calcium fly ash-based geopolymer concrete has excellent compressive strength, suffers very little drying shrinkage and low creep, excellent resistance to sulfate attack, and good acid resistance. It can be used in many infrastructure applications. One ton of low-calcium fly ash can be utilised to produce about 2.5 cubic metres of high quality geopolymer concrete, and the bulk price of chemicals needed to manufacture this concrete is cheaper than the bulk price of one ton of Portland cement. Given the fact that fly ash is considered as a waste material, the low-calcium fly ash-ased geopolymer concrete is,therefore, cheaper than the Portland cement concrete. The special properties of geopolymer concrete can further enhance the economic benefits. Moreover, reduction of one ton of carbon dioxide yields one carbon credit and, the monetary value of that one credit is approximately 20 Euros. This carbon credit significantly adds to the economy offered by the geopolymer concrete. In all, there is so much to be gained by using geopolymer concrete.We are happy to participate and assist the industries to take the geopolymer concrete technology to the communities in infrastructure applications. We passionately believe that our work is a small step towards a broad vision to serve the communities for a better future.